Pengembangan Tes Diagnostik Menggunakan Certainty Of Response Index (CRI) Termodifikasi pada Materi Tekanan Zat untuk Siswa Kelas VIII SMP - Idayanti, Idayanti; Darsono, Teguh; Naini M, Budi (UPEJ Unnes Physics Education Journal, 2019)
Mastery of physics concepts student in Indonesia is still relatively low which can lead to misconceptions. Diagnostic tests using the Certainty of Response Index (CRI) is one of the most effective and feasible methods to identify misconceptions. This study aims to determine the characteristics of the diagnostic test that is produced and describe the misconceptions on matter pressure subject. The type of research is a development research (Research and Development). The product of this research is a diagnostic test for second grade junior high school which the subject is matter pressure. Research respondents were students of SMP N 2 Kaliwungu class VIII B, VIII D and VIII E. The results showed that diagnostic test products were 15 questions consisting of 1 easy question, 7 moderate questions and 7 difficult questions and had a reliability coefficient of 0.629. The resulting diagnostic tests can be used to reveal student misconceptions. The highest misconception occurs in the application of Archimedes law which is 69%. Students assume that the volume of melting ice cubes will increase the volume of water in the glass.